2009
DOI: 10.1080/13698240903403915
|View full text |Cite
|
Sign up to set email alerts
|

Of Rain and Raids: Violent Livestock Raiding in Northern Kenya

Abstract: In the face of the current focus on climate change, the question whether climate variations have effects on ethnic violence is addressed. This article shows the results of an empirical study on the relationship between violent livestock raiding and climatic conditions. The practice of livestock raiding causes large numbers of casualties in northern Kenya. While conflicts over scarce resources may be largely explained by drought conditions, population pressure, and access problems, livestock raiding is more vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 7 publications
(10 reference statements)
4
79
0
1
Order By: Relevance
“…Hunger among pastoral households in the study area is mostly associated with the dry season. This results from different interrelated factors, including the deteriorated condition of livestock due to scarcity of water and pasture (Witsenburg and Adano 2009). During the dry season, milk production, which forms an essential component of the pastoral household diet in the wet seasons, is drastically reduced (Ilatsia et al 2007).…”
Section: Contribution Of Camel Milk To Household Food Basketsmentioning
confidence: 99%
“…Hunger among pastoral households in the study area is mostly associated with the dry season. This results from different interrelated factors, including the deteriorated condition of livestock due to scarcity of water and pasture (Witsenburg and Adano 2009). During the dry season, milk production, which forms an essential component of the pastoral household diet in the wet seasons, is drastically reduced (Ilatsia et al 2007).…”
Section: Contribution Of Camel Milk To Household Food Basketsmentioning
confidence: 99%
“…Natural resources usually seem like the obvious cause, but conflict may be triggered by the absence of good institutions and external interference. A study of Northern Kenya found that it is not drought, but the coming of the rains that is associated with greater conflict casualties (Witsenburg & Adano, 2009). Pastoralists do not fight during a time of scarcity but during periods of plenty, and the disruption of livelihoods remains a major concern for security policies.…”
Section: Natural Resource Wealth Climate Change and Violent Conflictmentioning
confidence: 99%
“…Violence in Colombia intensifies when coca or oil prices rise (Angrist and Kugler, 2008;Dube and Vargas, 2013), livestock raiding in Kenya intensifies when herds are healthy (Witsenburg and Adano, 2009), and Japan's long recession has cut into the yakuza's profits from racketeering (Hill, 2006, p. 247). The dynamics of the slave trade, then, followed a logic similar to the model of Besley and Persson (2011); greater state revenues encouraged repression (slave raiding) under non-cohesive political institutions.…”
Section: Introductionmentioning
confidence: 99%